Improvement of Caciotta-like cheese nutritional value by means of enrichment with blackcurrant (Ribes nigrum) and Cornelian cherry (Cornus mas) - Andersen, Jonas; Bosetti, Maddalena; Mancini, Andrea; Solovyev, Pavel; Nardin, Tiziana; Bontempo, Luana; Larcher, Roberto; Franciosi, Elena (Frontiers in Nutrition, 2023)
In this study we supplemented models of Caciota-like cheese with blackcurrant (Ribes nigrum) and cornelian cherry (Cornus mas), as they have high content of polyphenols, known as phytochemicals associated with health benefits. We evaluated the microbial composition, organoleptic aspects, total phenolic content and chemical composition of model-cheeses enriched with blackcurrant and cornelian cherry. Two different suppliers were tested: a conventional and an organic one, and two different conditions of preparation (freeze-dried, not freeze-dried) were tested in two different amounts (0.3% and 0.6% dry weight w/v milk volume). The enrichments did not affect the acceptance of the cheese, neither by blackcurrant nor by cornelian cherry incorporation, with the exception of the appearance.. We showed that the enrichments with blackcurrant and cornelian cherry increased total polyphenol content in our cheeses, in particular when blackcurrant and cornelian cherries from conventional farming. Blackcurrant enriched cheeses showed higher counts of lactic acid bacteria, higher levels of organic acids, amino acids, gamma-aminobutyric acid, histamine and lower amount of monosaccharides deriving from bacterial lactose fermentation in cheese, suggesting a positive effect of blackcurrant compounds on the growth and activity of lactic bacteria. Overall, we showed that cheeses enriched with blackcurrant or cornelian cherry from conventional farming, increased the bioactive potential of the dairy product without having adverse effect on the microbial community, physiochemical properties or on the organoleptic properties. taste/smell.